PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORT DAN LEVERAGE TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Empiris pada Perusahaan Sektor Pertambangan yang terdaftar di BEI Tahun 2012 – 2017) - Liina Hasna Hidayah; Dewi Saptantinah Puji Astuti; Djoko Kristianto (Universitas Slamet Riyadi, 2020)
The Purpose of this research is to analyze (1) the effect of economic performance on corporate financial performance, (2) the effect of environmental performance on corporate financial performance, (3) the influence of social performance on corporate financial performance, (4) the influence of leverage on corporate financial performance using a ratio profitability (ROA). The population in this study are mining sector companies listed on the Stock Exchange in 2012 – 2017. The number of companies sampled in this study were 10 companies. The data collection method used is the documentation method. The technical analysis of the data used in this study is multiple linear regression. The results of this study indicate that the disclosure of economic performance partially does not affect financial performance in a positive direction, partial disclosure of environmental performance does not affect financial performance with negative direction, partial disclosure of social performance does not affect financial performance with positive direction and partial leverage significant effect on financial performance with negative direction. Simultaneously Sustainability Report disclosure and leverage have a significant effect on the company's financial performance